2021
DOI: 10.1371/journal.pone.0251256
|View full text |Cite
|
Sign up to set email alerts
|

Testis structure, duration of spermatogenesis and daily sperm production in four wild cricetid rodent species (A. cursor, A. montensis, N. lasiurus, and O. nigripes)

Abstract: Although rodents represent approximately 40% of all living mammalian species, our knowledge regarding their reproductive biology is still scarce. Due to their high vulnerability to environmental changes, wild rodents have become beneficial models for ecological studies. Thus, we aimed to comparatively investigate key functional testis parameters in four sexually mature wild rodent species (A. cursor, A. montensis, N. lasiurus, and O. nigripes). These species belong to the Cricetidae family, which is the most d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(85 reference statements)
0
2
2
Order By: Relevance
“…birds [Garamszegi et al, 2005], mammals [Cordeiro et al, 2021;Møller, 1989] and insects [Hayward & Gillooly, 2011]), however, it contrasted with our intraspecific results in which only one of the six focal species, P. gossypinus, showed a correlation between testes size and sperm count across males. Notably, we found that variation in both of these traits is greater across than within species, which can make correlations more likely to be detected (Mincey, 2018) and, thus, may account for the differences between our inter-and intraspecific analyses.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…birds [Garamszegi et al, 2005], mammals [Cordeiro et al, 2021;Møller, 1989] and insects [Hayward & Gillooly, 2011]), however, it contrasted with our intraspecific results in which only one of the six focal species, P. gossypinus, showed a correlation between testes size and sperm count across males. Notably, we found that variation in both of these traits is greater across than within species, which can make correlations more likely to be detected (Mincey, 2018) and, thus, may account for the differences between our inter-and intraspecific analyses.…”
Section: Discussioncontrasting
confidence: 93%
“…This pattern has been observed in a number of interspecific comparative studies (e.g. in fish [Stockley et al, 1997 ], reptiles [Friesen et al, 2017 ], birds [Garamszegi et al, 2005 ], mammals [Cordeiro et al, 2021 ; Møller, 1989 ] and insects [Hayward & Gillooly, 2011 ]), however, it contrasted with our intraspecific results in which only one of the six focal species, P . gossypinus , showed a correlation between testes size and sperm count across males.…”
Section: Discussioncontrasting
confidence: 58%
“…Studies estimate that 4-8 × 10 7 spermatozoa are produced per gram of testis in mice. 43,44 Considering that the weight of the murine testis is approximately 0.1 g, 45 roughly 5 million spermatozoa are produced per testis per day. As a significant number of spermatozoa are constantly produced at the closed-end of the male reproductive system, they are expelled from the other open-end of the tract.…”
Section: Origins Of Luminal Flowmentioning
confidence: 99%
“…Spermatogonial stem cells located in the seminiferous tubules of the testis continuously give rise to spermatozoa after sexual maturation until death. Studies estimate that 4–8 × 10 7 spermatozoa are produced per gram of testis in mice 43,44 . Considering that the weight of the murine testis is approximately 0.1 g, 45 roughly 5 million spermatozoa are produced per testis per day.…”
Section: Luminal Fluid Dynamics In Mature Epididymismentioning
confidence: 99%